Rancang Bangun Aplikasi Elektronik Transportasi Bandara Yogyakarta International Airport Berbasis Mobile Menggunakan Android Studio - Candra Agustina; Sardiarinto Sardiarinto (Jurnal Teknologi Informasi dan Terapan, 2020)
Abstract— Yogyakarta International Airport is a new airport in Yogyakarta, located in Temon, Kulonprogo Regency. Yogyakarta International Airport began operations on May 6, 2019. It was marked by the first landing of Citilink from Halim Perdanakusuma Jakarta. To support airport operations, the Transportation Department also prepares supporting transportation modes, such as airport trains, Damri Buses and, Shuttle Bus to get to the Airport. This mode of transportation connects cities around the airport, such as Purworejo, Magelang, Yogyakarta City, and even Surakarta City. However, because the airport is still relatively new, the information obtained by the public is still minimal. Therefore an informative application is needed for prospective passengers to go to or leave the airport. The application is made based on mobile, by utilizing GPS technology to monitor the position of the vehicle in real-time. This application will make it easier for visitors to travel to areas around YIA Airport.